2012
DOI: 10.1089/ten.tea.2011.0360
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Three-Dimensional Hydrogel Matrix Carrying Basic Fibroblast Growth Factor for the Cultivation of Mesenchymal Stem Cells and Osteogenic Differentiation

Abstract: Three-dimensional (3D) collagen hydrogels have been extensively used for cell culture experiments and are more closely representative of in vivo conditions than monolayer (2D) culture. Here we cultured rat bone marrow-derived mesenchymal stem cells (MSCs) in collagen hydrogels containing varying concentrations of basic fibroblast growth factor (bFGF) to examine the effect of bFGF on MSC proliferation and osteogenic differentiation in 3D culture. The optimal bFGF concentration that promoted the greatest degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 79 publications
3
61
0
Order By: Relevance
“…64,65 The results suggested that gel contraction was due to the interaction of cells with the hydrogel fibers which along with the production of extracellular matrix resulted in the remodeling of fibrous gel structure. [64][65][66] When cells adhered onto the hydrogel fibers through integrin-adhesion complexes, tensile forces are created between cells and the surrounding matrix. 65 Once cells migrate within the hydrogel, fibers are rearranged, resulting in gel contraction.…”
Section: Figmentioning
confidence: 99%
“…64,65 The results suggested that gel contraction was due to the interaction of cells with the hydrogel fibers which along with the production of extracellular matrix resulted in the remodeling of fibrous gel structure. [64][65][66] When cells adhered onto the hydrogel fibers through integrin-adhesion complexes, tensile forces are created between cells and the surrounding matrix. 65 Once cells migrate within the hydrogel, fibers are rearranged, resulting in gel contraction.…”
Section: Figmentioning
confidence: 99%
“…The substrate is critical, so for example human pluripotent cells are often plated onto Mouse Embryonic Fibroblast (MEF) feeders [1,2] or are specially adapted for survival and growth on acellular material such as matrigel [3]. In addition to substrate, Initial Cell Seeding Density (ICSD) can have a significant impact on cell behaviour and is reported to alter proliferation and differentiation responses of various adult cells during 2D culture [4] and in 3D culture for tissue engineering purposes [5]. In the case of pluripotent cells, passaging hESC colonies at lower density of 1:8 resulted in a high degree of spontaneous differentiation versus those passaged at high density of 1:3 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, several biomaterials were investigated as supporting matrix for bone tissue engineering, such as alginate and nanofibers [9][10][11]. Collagen, a natural extracellular matrix, has a good biocompatibility for stem cells survival and could form hydrogels in situ to retain cells and thus was widely used in tissue engineering, including bone tissue engineering [12][13][14]. For enhancing the therapeutic effects, it is essential to guarantee the osteogenic differentiation of seeding cells within scaffolds [14].…”
Section: Introductionmentioning
confidence: 99%
“…Collagen, a natural extracellular matrix, has a good biocompatibility for stem cells survival and could form hydrogels in situ to retain cells and thus was widely used in tissue engineering, including bone tissue engineering [12][13][14]. For enhancing the therapeutic effects, it is essential to guarantee the osteogenic differentiation of seeding cells within scaffolds [14]. However, pure collagen itself was limited in guiding osteogenic differentiation of stem cells.…”
Section: Introductionmentioning
confidence: 99%